Public Administration in the Field of Public Health Protection in the New Paradigm of Public Authority: Problems of Correlation Between Constitutional and Administrative Law Regulation - E. V. Epifanova (Сибирское юридическое обозрение, 2022)
The article is devoted to the study of the problems of correlation between the constitutional-legal and administrative-legal regulation of public administration in the field of public health protection in the system of social administration. The purpose of the article is to identify the relationship between the subject of regulation of constitutional and administrative law in the field of public administration in terms of health protection in the system of social administration, to identify its distinctive features. The goal was achieved with the help of general scientific methods (analysis, synthesis, dialectical, historical and legal method) and the formal legal method. State administration is carried out constantly, regardless of the presence or absence of a constitution in a particular state, other constitutional acts, and even in the absence of constitutional ideas, as was the case in Russia until the 19th century. The concept of administrative and legal regulation of public administration in the field of public health in modern conditions is based on constitutional norms on the right of citizens to health protection and medical care (Article 41 of the current Constitution of the Russian Federation), as well as on the norms on the organization of public power in the Russian Federation. Analyzing the content of the legal literature, the current legislation, the Author came to the conclusion that for the analysis of the correlation between the concepts of constitutional and legal and administrative-legal regulation in the field of health care, the provisions of Art. 71 and 72 of the Constitution of the Russian Federation. In particular, assigning the organization of public authority to the federal center, the Constitution of the Russian Federation thereby predetermines the principles of organization of the public administration system in the field of health care. In addition, Art. 71 of the Constitution of the Russian Federation leaves the federal authorities in charge of establishing a unified legal framework for the healthcare system, which is being transformed into legislative and subordinate regulation, including issues of managing the healthcare system. Administrative law, due to the wide possibilities of operational by-law regulation, is characterized by taking into account the latest achievements in the natural and human sciences in industry standards, sometimes faster than the legislator does.